2018
DOI: 10.1093/mnras/sty175
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the SN Refsdal host revealed by MUSE: a regularly rotating spiral galaxy at z ≃ 1.5

Abstract: We use Multi Unit Spectroscopic Explorer (MUSE) observations of the galaxy cluster MACS J1149.5+2223 to explore the kinematics of the grand-design spiral galaxy (Sp1149) hosting the SN "Refsdal". Sp1149 lies at z 1.49, has a stellar mass M * 5×10 9 M , a star-formation rate SFR 1 − 6 M yr −1 and represents a likely progenitor of a Milky-Way-like galaxy. All the four multiple images of Sp1149 in our data show strong [O ii]-line emissions pointing to a clear rotation pattern. We take advantage of the gravitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Several authors have shown indeed that, if the effect of beam smearing is properly taken into account, the velocity dispersions in distant galaxies are comparable to or only slightly larger than in local galaxies (e.g. Di Teodoro et al 2016Teodoro et al , 2018Lelli et al 2018).…”
Section: Gravitational Energymentioning
confidence: 99%
“…Several authors have shown indeed that, if the effect of beam smearing is properly taken into account, the velocity dispersions in distant galaxies are comparable to or only slightly larger than in local galaxies (e.g. Di Teodoro et al 2016Teodoro et al , 2018Lelli et al 2018).…”
Section: Gravitational Energymentioning
confidence: 99%
“…Moreover, the remaining SN energy could be spent to drive galactic winds (e.g. Fraternali et al 2004;Veilleux et al 2005;Rubin et al 2014;Cresci et al 2017;Di Teodoro et al 2018;Armillotta et al 2019).…”
Section: Galaxymentioning
confidence: 99%
“…We optimize the strong-lensing model (cluster mass and cosmological) parameters with uniform priors, over the positions of 89 observed and reliable multiple images belonging to 10 different sources (1.240 ≤ z ≤ 3.703) and to 18 knots of the SN Refsdal host (z = 1.489), further validated by MUSE velocities from [O II] emission (see Figures 8 and 9 in G16 and Di Teodoro et al 2018). As detailed in G16, the considered positional uncertainty of each image is 0.26 ′′ in order to get a χ 2 value that is comparable to the number of the degrees of freedom (except for the 5 multiple images of SN Refsdal, S1-S4 and SX, for which we use 0.13 ′′ ).…”
Section: Lensing Observablesmentioning
confidence: 99%